A PERANCANGAN APLIKASI INVENTARIS BARANG MILIK NEGARA BERBASIS WEB PADA DEPUTI BIDANG PENCEGAHAN BNN - Sumaryanto; Sumarna Sumarna (Jurnal Informatika Teknologi dan Sains, 2022)
At the Deputy for Prevention of the National Narcotics Agency, the recording of inventory of goods on loan is still done manually using Microsoft Excel, causing problems in finding inventory and processing data. To find out what items have been lent and to whom, the officers must track down the BAST (Minutes of Handover of Goods) which are made so that they become inefficient. Therefore, it is necessary to make an application for the inventory of state-owned goods that can be used to manage and record the inventory of goods that exist and have been lent. So that related parties no longer have difficulty if they want to monitor the inventory of goods that are still there or if they want to track goods that have been lent to a second party.